2015
DOI: 10.1080/14680629.2015.1030911
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the microstructure of recycled asphalt shingle binder and its blending with virgin bitumen

Abstract: Recycling waste roofing shingles into pavement construction has attracted more attention due to their high content of usable bitumen. Waste roofing shingles have gone through an airblowing process during production and are exposed to severe weather for many years during service life, which yields extremely aged asphalt binder. The difference in nature between virgin binder and binder from recycled asphalt shingle (RAS) has led to concerns over binder blending and compatibility of asphalt paving mixtures contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Allen et al reported that the dispersed phase (i.e., bee) increased as saturate fractionate in the asphalt increased [28]. e dispersed phase can completely change when a virgin asphalt is mixed with aged asphalt binder from either recycled asphalt pavement or roof shingles; microparticles found in the interfacial zone ranged from 160 nm to 2.07 µm by recent multiple studies [29,30], as presented in Figure 8 [31].…”
Section: Analysis Of Morphological Phases Of Asphaltmentioning
confidence: 99%
“…Allen et al reported that the dispersed phase (i.e., bee) increased as saturate fractionate in the asphalt increased [28]. e dispersed phase can completely change when a virgin asphalt is mixed with aged asphalt binder from either recycled asphalt pavement or roof shingles; microparticles found in the interfacial zone ranged from 160 nm to 2.07 µm by recent multiple studies [29,30], as presented in Figure 8 [31].…”
Section: Analysis Of Morphological Phases Of Asphaltmentioning
confidence: 99%
“…Considering the large specific surface area of mineral aggregates in an asphalt mixture, these effects cannot be undermined. Furthermore, with an increasing emphasis on the use of reclaimed asphalt pavement (RAP), there is a renewed interest in better understanding the influence of binder interactions with fresh aggregates and black rock on the properties of the binder and the mixture [10][11][12].…”
Section: Background and Motivationsmentioning
confidence: 99%
“…They consist of the assessment of the chemical properties of mixtures or the analysis of the microstructure of the bitumen film. Direct methods include, among others, FTIR spectrographic, GPC gel chromatography, X-ray spectroscopy or microscopy analysis [ 11 , 12 , 13 , 14 , 15 ]. The second group consists of indirect methods.…”
Section: Introductionmentioning
confidence: 99%